Transformational And Transactional Leadership Influence On Job Performance Through Mediating Of Knowledge Sharing: Ancored By Cor Theory - Mustaqfirin, Mustaqfirin; H, Sunarno; Sumekar, Kertati (Jurnal Studi Manajemen Bisnis, 2021)
ABSTRACT The study aims to examine more effective leadership styles which are the transformational or transactional leadership that influences on job performance through mediating of knowledge sharing serving as the role of energy resource based on the conservation of resources theory. Because of Pandemic Covid-19, the empirical evidence has come from employees at 1 to 5-star Hotels in Jawa Tengah to test our hypotheses by receiving a duplicate of e-Questionnaire submitting through email and WhatsApp messages by adding the link of google form. The sample was 111 respondents. Based on the results of the Structural Equation Model, transformational leadership does not influence significantly job performance. Furthermore, transactional leadership does not affect significantly job performance. Then, transformational leadership does not influence significantly knowledge sharing. However, transactional leadership affects significantly knowledge sharing. Moreover, knowledge sharing influences significantly job performance. Based on the mediation approach, knowledge sharing mediates between transformational leadership and job performance. In line with the harmony, knowledge sharing mediates transactional leadership and job performance. Therefore, to improve job performance, the organization has to apply the mediation of knowledge sharing between transformational leadership and transactional leadership.ABSTRAKPenelitian ini menguji kepemimpinan yang lebih efektif, apakah kepemimpinan transformasional atau kepemimpinan transaksional yang berpengaruh terhadap kinerja pekerjaan melalui mediasi berbagi pengetahuan yang berperan sebagai sumber energi berdasarkan teori konservasi sumber daya. Disebabkan situasi pandemi Covid-19, data empiris dikirimkan kepada karyawan hotel bintang 1- 5 se-Jawa Tengah untuk menguji hipotesis penelitian dengan cara responden menerima tautan permohonan pengisian e-kuesioner melalui pesan e-mail dan WhatsApp yang berisi link google form. Sampel penelitian ini berjumlah 111 responden. Berdasarkan hasil Model Persamaan Struktural, kepemimpinan transformasional tidak berpengaruh signifikan terhadap kinerja pekerjaan. Kemudian, kepemimpinan transaksional juga tidak berpengaruh signifikan terhadap kinerja pekerjaan. Selanjutnya, kepemimpinan transformasional tidak berpengaruh signifikan terhadap berbagi pengetahuan. Namun, kepemimpinan transaksional berpengaruh signifikan terhadap berbagi pengetahuan. Setelah itu, berbagi pengetahuan berpengaruh signifikan terhadap kinerja pekerjaan. Berdasarkan pendekatan mediasi, berbagi pengetahuan memediasi kepemimpinan transformasional dan kinerja pekerjaan. Sejalan dengan harmoni, berbagi pengetahuan memediasi kepemimpinan transaksional dan kinerja pekerjaan. Oleh karena itu, untuk meningkatkan kinerja pekerjaan, organisasi harus menerapkan mediasi berbagi pengetahuan antara kepemimpinan transformasional dan kepemimpinan transaksional.